MENGENAL TANAMAN OBAT KELUARGA (TOGA) ATAU OBAT TRADISIONAL DAN PENGGUNAANYA YANG AMAN DI DESA SIDOREJO - Irda Rizky Wiharti; Musa Fitri Fatkhiya; Belita Aura Priani Merin; Salsa Rara Sumbada; A'mirotul Hasnah; Ghefira Khoirina Putri; Tine Anistia Putri Pratama (Jurnal Pengabdian Masyarakat Berkelanjutan, 2026)
Family Medicinal Plants (Tanaman Obat Keluarga/TOGA) represent a community empowerment strategy to enhance family self-reliance in maintaining health through the cultivation and utilization of medicinal plants in home gardens. However, public knowledge regarding the types, benefits, processing methods, and safe use of TOGA remains limited. This community service program aimed to improve the knowledge of members of the Family Welfare Empowerment (PKK) organization in Sidorejo Village regarding the utilization of TOGA and the rational and safe use of traditional medicines. The program was conducted on June 17, 2026, at the Sidorejo Village Hall, Warungasem District, Batang Regency, involving PKK members as participants. The educational intervention employed lectures, interactive discussions, question-and-answer sessions, quizzes, and evaluations using pretests and posttests. The results demonstrated that participants actively engaged in the educational activities, as reflected by their enthusiastic participation during discussions and improved posttest scores compared with pretest scores. These findings indicate that the educational program effectively enhanced participants' knowledge of medicinal plant species, their health benefits, cultivation techniques, processing methods, and the appropriate use of traditional medicines. This program is expected to encourage the community to sustainably cultivate and utilize TOGA as a promotive and preventive approach to improving family health.